Concerns, Mental Health, and Quality of Life in Living Kidney Donation–Parent Donor Candidates Worry Less about Themselves - Pérez-San-Gregorio, M. Ángeles; Martín-Rodríguez, Agustín; Luque-Budia, Asunción; Conrad, Rupert (Frontiers in Psychology, 2017)
Even though the majority of living kidney donor candidates appear in good mental health and show few concerns little is known concerning the influence of the type of donor-recipient relationship on donor candidates specific concerns with regard to kidney donation. 136 donor candidates at Virgen del Rocío University Hospital of Seville filled in the Scale of Concerns Regarding Living Kidney Donation of whom 105 donor candidates and their corresponding recipients (105 patients with End-Stage Renal Disease) were further evaluated with regard to mental health (Hospital Anxiety and Depression Scale, Beck Depression Inventory-II) and quality of life (SF-36 Health Survey). As hypothesized recipients scored higher on depression and lower on quality of life. Donor candidates intending to donate to their children were significantly less concerned about risks of donation for themselves compared to donor candidates donating to siblings. Our findings highlight the importance of the type of donor-recipient relationship to understand specific concerns of donor candidates and optimize psychosocial assessment and support. From an evolutionary perspective parents lack of concern about their own well-being can be seen as an altruistic behavior to increase children’s fitness at the (potential) expense of their own fitness.